Special Issue—Biosensors and Neuroscience: Is Biosensors Engineering Ready to Embrace Design Principles from Neuroscience? - Grace M. Hwang; Aleksandr L. Simonian (Biosensors, 2024)
In partnership with the Air Force Office of Scientific Research (AFOSR), the National Science Foundation’s (NSF) Emerging Frontiers and Multidisciplinary Activities (EFMA) office of the Directorate for Engineering (ENG) launched an Emerging Frontiers in Research and Innovation (EFRI) topic for the fiscal years FY22 and FY23 entitled “Brain-inspired Dynamics for Engineering Energy-Efficient Circuits and Artificial Intelligence” (BRAID) [...]